How Does Board Gender Diversity Impact Firm Performance? The Mediation Effect of Dividend Payout Ratio - Candy, Candy; Joycelin, Joycelin; Hesniati, Hesniati; Cuandra, Fendy (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
This study looks at how the dividend payout ratio acts as a mediating factor between the impact of gender diversity on the board and firm performance. The percentage of female commissioners, female executive directors, female independent directors, and female directors served as a proxy for board gender diversity. In the meantime, return on equity and assets are used to gauge the company's performance. Using secondary data from the financial and annual reports of sample firms posted on the official IDX website (www.idx.co.id) and company websites, a quantitative technique was used to research companies indexed in the IDX High Dividend 20 between 2018 and 2022. Panel regression is the analysis technique employed. The E-Views application is utilized for data processing and testing. Board gender diversity, especially the percentage of female directors (FDP), has a positive effect on the DPR. On the other hand, firm performance as measured through ROA and ROE is not influenced by DPR. The presence of female independent directors (FID) contributes positively to firm performance as measured through ROA, while firm performance as measured through ROE is positively influenced by female directors (FDP).